2016
DOI: 10.1002/slct.201600965
|View full text |Cite
|
Sign up to set email alerts
|

Dual Behaviour of Amorphous Carbon Released Electrochemically from Graphite

Abstract: Here we show that the main product released from graphite in the early stages of the anodic polarization is a carbon-based salt comprised of an amorphous carbonaceous material with delocalized negative charge, counterbalanced by sodium cations. Remarkably, this material shows a dual behaviour: it behaves as an electrolyte in aqueous medium, which has the ability to enhance the capacitive properties of the electrodesolution interface and in the solid state it can be used as an electrode material with meaningful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
(24 reference statements)
4
14
0
Order By: Relevance
“…Actually, no nanoparticles were detected (Figure S1 in the Supporting Information) unless the AFM analysis was performed with a non‐fresh EHC solution (Figure F,G). We speculate that by using a fresh EHC solution, a smooth film is formed, similar to those found for EHC synthesised in phosphate buffer . With the non‐fresh EHC solution, the observation of round carbon domains, mostly <2 nm in diameter with a thickness <0.6 nm, suggested that they form by aggregation of carbon clusters over time.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Actually, no nanoparticles were detected (Figure S1 in the Supporting Information) unless the AFM analysis was performed with a non‐fresh EHC solution (Figure F,G). We speculate that by using a fresh EHC solution, a smooth film is formed, similar to those found for EHC synthesised in phosphate buffer . With the non‐fresh EHC solution, the observation of round carbon domains, mostly <2 nm in diameter with a thickness <0.6 nm, suggested that they form by aggregation of carbon clusters over time.…”
Section: Resultssupporting
confidence: 65%
“…Electrogenerated hydrophilic carbon (EHC) nanomaterials, recently developed in our group, might potentially emerge as materials that can overcome the above‐mentioned constraints . This type of nanomaterial, displaying outstanding solubility in water, is released from graphite in the early stages of a galvanostatic polarisation in a two‐compartment cell (Figure A), in a low‐cost, simple, green and fast procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D‐assembly may result from the self‐assembled aggregation of the sub‐units that compose the EHC due to strong intermolecular affinities. On the basis of our previous results, electrostatic interactions between oppositely charged species (sodium cations and negative charged carbon‐based nanomaterial) should be the main driving force to form the self‐assembled aggregations. Control experiments with Pt as the anode or cathode electrode allow confirming that EHC could be either generated at the cathode as well as at the anode of graphite (Figure d and 1e′).…”
Section: Resultsmentioning
confidence: 72%
“…This process promotes the removal of oxidation debris through the repulsion created between the negative charge of the deprotonated debris and the negative charge of the deprotonated surface functional groups of the graphene‐based material. Recently, a simple methodology to produce amorphous hydro‐soluble carbon nanomaterials in one single step was developed by our group based on an electrochemical approach . It was found that this raw material was the major product released at the anodic compartment in the early stages of the galvanostatic polarization using graphite electrodes.…”
Section: Introductionmentioning
confidence: 99%